Factors influencing the vitamin d status of adolescents in Johannesburg, and its effects on body composition - Poopedi, Machuene Ananias (My University, 2021)
Introduction Sunlight is nature‘s gift to human beings in the cutaneous production of vitamin D. However, one of the challenges faced by public health in the majority of countries across the globe is hypovitaminosis D across all ages. Factors such as skin pigmentation, cloud cover, air pollution, increase in body fat content, an indoor lifestyle, and a lack of exposure of the skin to sunlight due to clothes covering the body, have been reported as responsible for hypovitaminosis D. The effects of this are rickets in children, osteomalacia in adults and osteoporosis in the elderly. Recent reports have found that vitamin D has functions in addition to bone health, including immune system benefits as well as cell proliferation, and differentiation. Furthermore, vitamin D status has been associated with a variety of diseases. However, the majority of reports have assessed vitamin D status by measuring it once, suggesting that vitamin D status is constant over the years, but this is far from the truth. Hence some researchers have suggested that vitamin D status should be measured longitudinally because of the factors involved. One challenging issue has been vitamin D laboratory assays that were reported to be inconsistent, which has led the researchers to call for standardization. There has been a lack of consensus among researchers in defining vitamin D status, thus some researchers‘ definition covers bone health and others use a definition which includes other organs beyond bone health. Studies of vitamin D status in children, its tracking over a period of time and its association with non-calcaemic diseases are a handful. Hence, the present study was aimed at assessing factors influencing vitamin D status, its tracking over 10 years and its effects on body composition in adolescents living in Johannesburg. Methods The group of children who formed the basis of my studies are the Bone Health sub-cohort of the Birth to Twenty cohort. This is a longitudinal study of child health and development, which has followed the development of 3273 children in the Greater Johannesburg area of South Africa since their birth in 1990. For anthropometric measurements and body composition, height was measured in millimetres (mm) using a wall-mounted stadiometer (Holtain, UK) and weight in kilograms (kg) using a digital electronic instrument (Dismed, USA). Both instruments were regularly calibrated and subjects wore minimal clothing when being weighed. Body mass index IX (BMI) was calculated as weight (in kg)/height2 (in m). Total fat mass and lean mass were measured by DXA, using Hologic QDR 4500 (Hologic Inc, Bedford, MA, USA). Factors influencing the vitamin D status of 10-year-old urban South African children were studied. Vitamin D status was assessed in 385 subjects because there were blood samples available. Furthermore, vitamin D tracking over a ten year period was conducted in 504 subjects; of these 99 subjects met the criteria of being available at the study site for a minimum period of 3 or more years. For an assessment of the association of the vitamin D status with non communicable disease risk in children, variables were measured in years 11, 12 13, 15 and 18-20 years. The variables assessed included anthropometry (weight, height and BMI), blood pressure (SBP and DBP) and 25(OH)D levels. The lipid levels (TC, Trig, HDL-C, and LDL-C) were only measured in year 12 and 18-20 year old participants. For age related changes between the two time points, year 12 participants (N = 261) were matched with those available in year 18-20 (N = 368) resulting in 200 in each group. The data for longitudinal analysis using the GEE comprised of the following groups of subjects, namely Year 11 (N = 288), Year 12 (N = 253), Year 13 (N = 292), Year 15 (N = 238) and Year 18-20 (N = 368). Results In 10-year-old children, white children had significantly higher 25(OH)D than their black peers (120  14.7 nmol/L and 93  13.4 nmol/L respectively; p = 0.0001). Seasonal variations in 25(OH)D levels were found only in the white group of children, with 25(OH)D levels being significantly higher in white than black children during the autumn and summer months (p = 0.01 and p = 0.0001 respectively). During vitamin D tracking, no significant correlation between 25(OH)D in the earlier and later years of adolescence was found, although there were significant correlations between year 11 and year 13 (r = 0.71; p < 0.0001), and between years 15, 17 and 20 (r ≥ 0.65; p < 0.0001). The percentage of adolescents whose 25(OH)D concentration changed by > 20 nmol/L from year 11 was calculated for all age groups: 12% of the cohort had a change of > 20nmol/L at 13 years of age compared to 46% at 20 years of age. Just more than one-half (53%) of the cohort changed their category of vitamin D status between the ages of 11 and 20 years; one-third of adolescents changed their vitamin D status from being replete to insufficient over the same period. X In assessing the association of vitamin D status with non-communicable disease risk, there were significant increases of mean BMI, BP and decreases in 25(OH)D levels with age (all p-values < 0.0001). In females, systolic BP was significantly higher in older participants (18-20 years of age) than younger participants (12 years of age), but 25(OH)D was significantly higher in younger than older participants. In males, there was a significant increase in BP in participants between the ages of 12 years and 18-20 years. 25(OH)D, total cholesterol (TC), and low density lipoprotein (LDL-C) were significantly lower in 18-20 year old participants compared to 12 year old participants. Longitudinally, 25(OH)D was only associated inversely with LDL-C. Conclusion The majority of children aged 10 years (74%) had ―sufficient‖ vitamin D status (25(OH)D > 75 nmol/L). Thus routine vitamin D supplementation is not warranted in children residing in the Johannesburg area but it is unknown whether similar results would be obtained in regions that are further south (such as Cape Town) or in inner city children living in crowded high-rise buildings. In the longitudinal study of vitamin D status, there was no long-term association between values obtained in the early years of adolescence and those of the later years. These results thus question the validity of those studies that have assessed the association of vitamin D status with disease outcomes, but in which vitamin D status was only measured once during the study. Finally, there was an increase in BMI and BP, and a decrease in 25(OH)D in adolescents followed longitudinally over a period of 10 years. After controlling for covariates, 25(OH)D was only significantly negatively associated with LDL-C, which suggests that vitamin D status might be associated positively with favourable lipid profiles in children and adolescents.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2021